Islamic Farming, Halal, Sustainability, and Farmer Welfare Impact - Haryono, Haryono (West Science Islamic Studies, 2024)
This study examines the impact of Islamic ethical farming practices, halal certification, and sustainable goat farming on the economic welfare of goat farmers in rural Indonesia. Using a quantitative approach, data were collected from 90 goat farmers through a structured questionnaire, and the results were analyzed using SPSS version 25. The findings reveal that all three independent variables—Islamic ethical farming practices, halal certification, and sustainable goat farming—positively and significantly influence the economic welfare of goat farmers. Sustainable farming practices had the strongest effect, followed by halal certification and Islamic ethical farming. The study concludes that integrating ethical, religious, and sustainable practices enhances the productivity, marketability, and long-term viability of goat farming operations, thereby improving farmers' economic welfare. These results offer valuable insights for policymakers and practitioners seeking to promote sustainable and ethical agriculture.